Pengembangan E-LKPD Flipbook Berbasis Realistic Mathematic Education (RME) untuk Memfasilitasi Kemampuan Literasi Matematis - Nazillatussyarifah, Fiya; Asyhar, Beni (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study was motivated by the low level of mathematical literacy skills, which is caused by the unequal distribution of learning materials. The purpose of this research is to determine the validity, practicality, and effectiveness of an RME-based flipbook E-Worksheet (E-LKPD) in facilitating mathematical literacy skills. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include questionnaires, observation sheets, and test items, while data analysis involves qualitative descriptive analysis and quantitative descriptive analysis.The results of this research and development show that: (1) the validity of the learning media obtained percentages of 91.3% and 87.4%, indicating that the media are valid; (2) the practicality of the learning media obtained percentages of 78.6% and 87.5%, indicating that the media are practical; and (3) the effectiveness of the learning media obtained an average percentage of 87.9% with a classical mastery level of 88.8%. Furthermore, the results of the students’ response questionnaires and observation sheets reached 85.3% and 100%, respectively. This means that the learning media are effective to be used in the learning process.